Coarse Tea and Insipid Rice: The Politics of Food in the Northern Song Period. (3rd July 2017) - Yue, Isaac
Abstract : This article investigates the politics of eating during the Northern Song period. In particular, it aims to consider the historical-political circumstances that gave rise to two polarizing schools of gastronomic practices: the excessive gourmands who viewed food as an expression of wealth and social status and the frugal literati who condemned this gustatory indulgence as unvirtuous and morally improper. In doing so, it hopes to shed light on the extent to which gastronomy during the Song Dynasty could be understood as a form of social and philosophical expression.